BLIND AND VISUALLY IMPAIRED PERSONS IN HEALTH CARE: ANALYSIS OF PROBLEMS AND POTENTIAL SOLUTIONS - Brestovacki Svitlica, Branislava (HEALTH CARE, 2023)
The aim of this review is to analyze, based on relevant scientific sources, the problems faced by blind and partially sighted people in health care, as well as to identify opportunities for solutions to these challenges. Blindness and visual impairment are serious health conditions that can significantly affect an individual's quality of life. These individuals often face numerous challenges when accessing health care. Accessibility of the physical environment, communication with healthcare professionals, access to information, and use of medical devices are some of the key issues. Improving access to health care can be realized through the application of technological solutions, education of health workers, provision of accessible communication and information, and the inclusion of blind and partially sighted people in health care planning.
Keywords: blind, visually impaired, health care, quality of life